Analytical and Experimental Investigations on Mechanical Properties of Weak Plane Bedding in Mudstone. (4th June 2021) - Zeng, Yijin; Jiang, Hailong; Ding, Shidong; Chen, Junhai; Wang, Yi; Zheng, Jie
Abstract : Wellbore instabilities frequently occur in mudstone formation with weak plane bedding because of strong anisotropies. The mechanics parameters of weak plane bedding are of vital significance to the wellbore stability analysis for mudstone formations. The conventional method for determining the mechanics parameters is to fit lots of triaxial test data due to the blindness of coring. In this paper, an evaluation method of the mechanics parameters of weak plane bedding is proposed to improve the accuracy of weak plane bedding mechanical properties. The mechanics parameters of weak plane bedding are obtained by combing the single-weak plane failure criterion with the compressive strength of rock obtained by the triaxial test of cores with different coring angles. It is seen that the new evaluation method is simple and convenient. On the other hand, a validation method of the mechanics parameters of weak plane bedding is proposed to ensure their accuracy. The compressive strength obtained from the core with the special coring angle is compared with the theoretical compressive strength for verifying the accuracy of weak plane bedding mechanical properties. It is observed that the proposed evaluation and validation methods can be used to measure the value of weak plane bedding mechanical properties precisely. The proposed methods are general and can be used for measuring the mechanical properties of fracture weak-plane and joint weak-plane.